ANALISIS KONTROL KUALITAS DENGAN METODE SIX SIGMA UNTUK MENCEGAH PRODUK CACAT PADA KERIPIK PISANG - Fikry, Havid; Muflihah, Nur (Fakultas Teknik Universitas Wisnuwardhana, 2021)
UKM 99 is a company that produces snacks made from nature, after the COVID-19 pandemic in the industrial world, both in services and manufacturing, there have been many changes. Each company develops each other to dominate the market. In terms of customer satisfaction and the quality of the products produced, the company makes improvements to the quality that has been applied. In UKM 99 which the author studied there were many problems with the quality of production, namely product defects, including: charred, thickness of chips, frying errors. The purpose of this study was to determine the cause of product defects in banana chips produced by UKM 99. Six sigma is a method of quality control and improvement. By using the six sigma method, it can be seen how the quality of banana chips produced by UKM 99. The six sigma approach in this study can be said that there are three causes of the highest product failure, namely: banana chips by 35.85%, thickness and frying techniques each percentage namely 33.96% and 30.19%